LncRNA MALAT1 Promote Cell Proliferation and Invasion by sponging miR-125b to Modulate HMGA1 Expression in Laryn-gocarcinoma - Guangxin Zong; Xinrong Feng; Xiuhua Sun; Jiexin Du; Guangsheng Wang; Tingting Song (Tehran University of Medical Sciences, 2021)
Background: Laryngocarcinoma is the most frequent head and neck malignant tumor. MALAT1 have a role in promoting cell proliferation and metastasis in several tumors. This research aimed to investigate the great roles of MALAT1in laryngocarcinoma. Methods: Overall, 54 cases of laryngocarcinoma tissues pathological specimens and paracancerous tissues were collected by surgical resection from the Department of Otolaryngology-Head and Neck Surgery at the Shandong Provincial Hospital affiliated to Shandong University, China from Jan 2012 to Oct 2015. The microRNA and protein levels of genes were evaluated by RT-qPCR and western blot. The proliferative and invasive ability were calculated usingCCK8 and transwell assays. Kaplan-Meier method was used to assess the survival of laryngocarcinoma patients. Results: In laryngocarcinoma tissues and cells, lncRNA MALAT1 expression was significantly increased compared to normal tissues and cells. LncRNA MALAT1 promotes proliferation and migration of laryngocarcinoma cells. LncRNA MALAT1 upregulates HMGA1 expression by acting as a competitive endogenous RNA (ceRNA) for miR-125b. Rescue experiments showed that microRNA-125b inhibitor reversed the change in cell viability and invasion induced by sh-MALAT1. Down regulation of lncRNA MALAT1 inhibits laryngocarcinoma proliferation and invasion by modulating miR-125b /HMGA1. Conclusion: LncRNA MALAT1 promotes the development of laryngocarcinoma by regulating the expression level of HMGA1 by acting as a miR-125b ceRNA and may be considered as a new strategy for the development of laryngocarcinoma.